PTU-067 Out-patient assessment for liver transplantation: a single centre experience. (28th May 2012) - Lim, T R; Armstrong, M J; Houlihan, D D; Wong, K; Cook, C; Turner, A; Perrin, M; Cantrill, J; Ashcroft, P; Hughes, D; Weijers, C; Holt, A
Abstract : Introduction: Assessment for orthotopic liver transplantation (LT) traditionally requires admission to hospital. In 2010, the liver unit at the University Hospital Birmingham (UHB) launched the first UK-based out-patient assessment programme (OPA). This study aims to describe our experience, with specific focus on feasibility, efficacy, cost-effectiveness and patient satisfaction. Methods: Patients undergoing elective LT assessment were retrospectively analysed between June 2010 and April 2011. Data collected included patient demographics/clinical features, LT assessment parameters, duration to listing/LT and reasons for LT refusal. An extensive cost evaluation was performed on both in- and out-patient LT assessment, including clinical tests, staffing and hospital facilities utilised. Patient satisfaction questionnaires were collected prospectively from April 2011 to November 2011. Results: 179 patients underwent LT assessment. 87/94 successfully completed OPA, with seven converted to in-patient LT assessment (IPA) due to pre-existing co-morbidity including refractory ascites and hepatic encephalopathy. All patients referred for OPA were triaged 2 weeks prior to the assessment to ensure suitability. 92 patients successfully underwent IPA. 66/87 OPAs were subsequently listed for LT (median duration from OPA to listing 3 days [0–306], of which 37/66 received a cadaveric graft. The reasons for OPAs not listed include: too early for LT (50.0%), contraindication to LT (42.9%) and patient refusal (7.1%). 53/92 IPAs were listed, mean duration 4 days [1–39], of which 34/53 were transplanted. Reasons for IPAs not listed: contraindication to LT (48.2%), too early for LT (44.4%) and patient refusal (7.4%). A single IPA costs on average £14 441 as compared to £11 494 for an OPA. Overall satisfaction (mean score 9.6/10; 10=very satisfied, 1=very dissatisfied) and convenience (7.9/10) for patients undergoing OPA were high. Conclusion: We describe for first time that OPA is feasible, efficient and cost-effective. With increasing demand on hospital beds in the UK National Health Service, such a programme has the potential to reduce the burden on LT in-patient services. Competing interests: None declared.